2000
DOI: 10.1177/014920630002600106
|View full text |Cite
|
Sign up to set email alerts
|

Does Cultural Socialization Predict Multiple Bases and Foci of Commitment?

Abstract: Some organizational commitment theorists have proposed that culture is an important antecedent to organizational commitment (Meyer & Allen, 1991; Wiener, 1982). This study tests whether individualized measures of power distance, collectivism, uncertainty avoidance, and masculinity are related to an employee’s level of commitment. A nine-factor model of commitment is postulated with three bases (affective, continuance, and normative commitment) and three foci (organization, supervisor, and workgroup) of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
312
3
19

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(349 citation statements)
references
References 50 publications
15
312
3
19
Order By: Relevance
“…Followers with high levels of anxiety and insecurity and low self-esteem primarily accept their leaders because they think they have to. These findings add to the commitment literature as they provide evidence that followers" characteristics specifically influence different components and foci of Personality and leadership 26 commitment (e.g., Clugston et al, 2000;. In conclusion, followers who show personality traits similar to transformational leaders are more likely to perceive transformational leadership and to develop higher levels of committed to their leader.…”
Section: Discussionsupporting
confidence: 56%
“…Followers with high levels of anxiety and insecurity and low self-esteem primarily accept their leaders because they think they have to. These findings add to the commitment literature as they provide evidence that followers" characteristics specifically influence different components and foci of Personality and leadership 26 commitment (e.g., Clugston et al, 2000;. In conclusion, followers who show personality traits similar to transformational leaders are more likely to perceive transformational leadership and to develop higher levels of committed to their leader.…”
Section: Discussionsupporting
confidence: 56%
“…Collectivism (alpha = .84) was measured with a five-item construct adapted from Clugston et al (2000). Participants indicated, on a scale from 1 = strongly disagree to 7 = strongly agree, the extent to which they perceived the importance of group welfare against individual benefits and gains.…”
Section: Methodsmentioning
confidence: 99%
“…Chiu (1999) found that individualists scored higher on positive affect and job satisfaction and lower on work strain than collectivists in a sample of Singaporean and HK nurses, who were significantly higher on COL and lower on IND than Australian and US nurses. Clugston et al (2000) assessed the relationships among Hofstede's four original cultural values and three bases (i.e., affective, continuance, and normative) and foci (i.e., organization, supervisor, and workgroup) of commitment using surveys in a US public agency. COL was positively related to affective commitment to supervisors and the workgroup, continuance commitment to the workgroup, and normative commitment to all foci; and PD was positively related to affective commitment to the organization and both continuance and normative commitment to all foci.…”
Section: Ocb (2)mentioning
confidence: 99%
“…Indeed, all 12 studies that included cultural values in addition to (or besides) IND-COL found significant effects. Of the five studies that included both IND-COL and other cultural values simultaneously (e.g., Earley, 1986;Clugston et al, 2000;Mitchell et al, 2000;Kirkman and Shapiro, 2001a;Harpaz et al, 2002), all explained unique variance beyond IND-COL. Such consistent findings suggest that including cultural values other than IND-COL in the other 52 Type I studies would have led to important insights.…”
Section: Research Challengesmentioning
confidence: 99%